1999
DOI: 10.1210/en.140.6.2533
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interactions Between Sex Steroids and Cytokines in the Human Pregnant Myometrium: Evidence for an Autocrine Signaling System at Term

Abstract: Little is known about the mechanisms controlling the expression of key proteins that regulate excitability and contractility in the human myometrium at term. However, evidence is accumulating to suggest that the cytokine transforming growth factor (TGF)beta may play a central role. TGFbeta1 and TGFbeta receptors are present in the myometrial cells, indicative of an autocrine signaling system. Furthermore, the levels of TGFbeta1 and the expression of its receptors increase in the myometrium at term suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 0 publications
1
23
0
5
Order By: Relevance
“…The different ability of cytokines to release PGs in several days of gestation may arise from diverse expression of receptors for particular cytokines in myometrium during pregnancy. To our knowledge, there are only data showing the expression of receptors for IL-1 and IL-8 in human myometrium at term (Hatthachote and Gillespie 1999). As we demonstrated here, cytokines used individually (at a dose of 1 and/or 10 ng/ml) increased more often the output of PGE 2 compared to PGF 2α from myometrial tissues.…”
Section: Discussionsupporting
confidence: 62%
“…The different ability of cytokines to release PGs in several days of gestation may arise from diverse expression of receptors for particular cytokines in myometrium during pregnancy. To our knowledge, there are only data showing the expression of receptors for IL-1 and IL-8 in human myometrium at term (Hatthachote and Gillespie 1999). As we demonstrated here, cytokines used individually (at a dose of 1 and/or 10 ng/ml) increased more often the output of PGE 2 compared to PGF 2α from myometrial tissues.…”
Section: Discussionsupporting
confidence: 62%
“…With respect to cytokine expression, estrogen in the high concentrations seen in pregnancy can inhibit proinflammatory pathways which include those activated by IL-1β (Polan et al, 1989), IL-6 (Keck et al, 1998, Kikuchi et al, 2000, IL-8 (Rodriguez et al, 2002) and TNF-α (Rogers and Eastell, 2001) as well as inhibiting the activity of natural killer cells (Seaman and Gindhart, 1979). In contrast, the secretion of 'anti-inflammatory interleukins' IL-4 (Kamada et al, 2001), IL-10 (Kanda and Tamaki, 1999) and transforming growth factor (TGF)-β (Hatthachote and Gillespie, 1999) are stimulated by estrogen in these high levels. Notwithstanding these clear anti-inflammatory effects of estrogen, in vivo estradiol can augment the production of pro-inflammatory cytokines by CD4+ T cells (Maret et al, 2003) likely via a direct effect as circulating leukocytes express ER-α (Straub, 2007).…”
Section: Page 13 Of 24mentioning
confidence: 99%
“…In placental trophoblasts and myometrial smooth muscle cells (SMCs), TGFb has been shown to up-regulate the expression of fibronectin, a marker of preterm labor (Goldenberg et al 1997. TGFbs mRNA and proteins are expressed in the human myometrium during menstrual cycle (Chegini et al 1994) and pregnancy , Kuscu et al 2001, and have been suggested to play a central role regulating excitability and contractility in the human myometrium at term (Hatthachote & Gillespie 1999).…”
Section: Introductionmentioning
confidence: 99%